English language teaching in Costa Rica: Facing challenges - Esquivel Cascante, Dawer (2022)
Undoubtedly, it is every teacher's life quest to find the best way to teach; there are no universal formulas to accomplish that. A committed teacher is a life-long learner, which shows why being an educator is not an easy career. A teacher is indeed like a candle that lights the students' path as it consumes itself. Such abnegation comes at a high price. Particularly, English teachers in a Country such as Costa Rica are faced with various challenges, ranging from deeply ingrained negative attitudes towards teachers and the education system itself, their own well-being which tends to be neglected a little too often, unequal access to resources and teaching materials, heterogeneous student populations, emotional factors in the classroom, among many others. An English teacher in a developing country (and probably elsewhere) has to be prepared to deal with the unexpected, learn, relearn, and unlearn, and whenever something new is learned, it is every (English) teacher's duty to share it using different means; getting published is but one way to do so. This ebook comprises a collection of essays written by students from the Master's Program in Education with an Emphasis on English Learning from Universidad Nacional, Costa Rica as part of their graduation project. In each of the manuscripts contained here, a Costa Rican English teacher reflects on some of his or her educational experiences and encountered challenges and proposes strategies to tackle them so that any English teachers out there facing similar situations may benefit from these ideas.